Deepfakes in Domestic and International Perspective - Ginsburg, Jane; Austin, Graeme (The Columbia Journal of Law & the Arts, 2025)
Have you always (or ever) yearned to produce your own recording of Elvis Presley singing great baritone arias from Italian opera? Or to make a movie starring Nicole Kidman as Lady Macbeth? Or a videogame featuring the bully who tormented you in high school suffering repeated tortures worthy of the Christian martyrdoms recounted with gusto in The Golden Legend? You can fulfill all these wishes, and more, thanks to the AI technology enabling the creation of “deepfakes”—known in legal documents as “digital replicas”—capable of simulating the visual and vocal appearance of real people, living or dead. AI programs can also generate musical compositions in the style of well- known composers or performers, as well as video sequences. What may be good fun in private may become pernicious, offensive, and even dangerous, if widely disseminated over social media or through commercial channels. But, at least in the U.S., legal protections for performers and ordinary individuals against digital replicas, are at best, scanty.